Determination of clavulanic acid in calf plasma by liquid chromatography tandem mass spectrometry - Reyns, Tim; De Baere, Siegrid; Croubels, Siska; De Backer, Patrick (Journal of mass spectrometry., 2006)
A method for the quantification of clavulanic acid in calf plasma using high‐performance liquid chromatography combined with electrospray ionization (ESI) mass spectrometry, operating in the negative ionization mode (LC‐MS/MS), is presented. Sample preparation includes a simple and fast deproteinization with acetonitrile and a back‐extraction of the acetonitrile with dichloromethane. Chromatography is performed on a reversed‐phase PLRP‐S polymeric column using 0.05% formic acid in water and acetonitrile. The limit of quantification is 25 ng/ml, which is lower than other published methods using ultraviolet (UV), fluorimetric or mass spectrometric detection. The limit of detection is calculated to be 3.5 ng/ml. The stability of clavulanic acid was demonstrated according to The Guidelines of Bioanalytical Method Validation of The Food and Drug Administration (FDA): freeze and thaw stability, short‐term stability, long‐term stability, stock solution stability and postpreparative stability. The method is used in a pharmacokinetic and bioequivalence study of amoxycillin/clavulanic acid formulations in calves. Copyright © 2006 John Wiley & Sons, Ltd.